Modified bronchial anastomosis in video-assisted thoracoscopic sleeve lobectomy: a report of 32 cases - Chen, Hao; Huang, Lin; Xu, Guobing; Zheng, Bin; Zheng, Wei; Zhu, Yong; Guo, Zhaohui; Chen, Chun (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Bronchial anastomosis is a key technical challenge in sleeve lobectomy, especially when using the video-assisted thoracoscopic surgery (VATS) approach. A retrospective study was conducted to evaluate the feasibility and safety of a modified bronchial anastomosis technique developed by the authors at Fujian Union Hospital. Methods: From October 2010 to October 2015, we performed 32 cases of VATS sleeve lobectomy through a three-port or single-port approach. All bronchial anastomoses were performed using modified bronchial anastomosis technique: the bronchial anastomosis was begun with an initial stitch on the posterior wall, and the bilateral quarters of the circumference were continuously sutured. The other two bilateral quarters were then similarly sutured, and the last knot was made outside the bronchial lumen. Results: All cases were completed uneventfully. No perioperative deaths or serious complications occurred. The mean operative time, bronchial anastomosis time, and blood loss volume were 271.8±67.5, 37.6±12.0 min, and 177.5±102.9 mL, respectively. The mean follow-up time was 21.0±11.7 months, and the follow-up rate was 96.9% (31/32). An electronic bronchoscope scan was performed 6 months after surgery, and a fine healing stoma was detected in all cases. No anastomotic fistula, anastomotic stenosis, or other serious postoperative anastomotic complications occurred until the end of follow-up. Conclusions: Modified bronchial anastomosis technique applied in bronchial anastomosis was safe and feasible in three-port and single-port VATS sleeve lobectomy with good short-term and long-term therapeutic results. Adequate management of the operative process and implementation of a skilled bronchial anastomosis technique could help to reduce the difficulty of VATS sleeve lobectomy.